IDEA AS ІMMANENT ESSENCE OF ACTION IN PHILOSOPHY OF RALPH EMERSON - Льовкіна, О. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The features of philosophical ground of action of R.Emerson are probed in the article.